Pd-catalyzed C-C bond-forming reactions of thymidine mesitylene sulfonate - Kang, Soon Bang; De Clercq, Erik; Lakshman, Mahesh K. (AMER CHEMICAL SOC, 2007)
Facile synthesis of C-4 aryl pyrimidinone nucleoside analogues from an easily prepared O-4-arylsulfonate derivative of thymidine is reported. Two O-4-arylsulfonylthymidine precursors, (4-methylphenyl)sulfonyl and (2,4,6-trimethylphenyl)sulfonyl, were prepared and analyzed for their stabilities. Of the two, the latter possessed suitable stability as well as reactivity for Pd-catalyzed C-C bond-forming reactions with a variety of arylboronic acids. These reactions at the C-4 position are nontrivial in comparison with similar reactions at the C-5 position of pyrimidine nucleosides, with hydrolysis of the arylsulfonate precursor being a competing reaction in some cases. There are pronounced solvent influences in these reactions, but successful reactions can be attained by careful control of conditions. Many reactions proceeded efficiently at room temperature, and electron-deficient arylboronic acids can also be cross-coupled under suitable conditions. Desilylation of these products was also nontrivial, and various conditions were tested. Finally, antiviral screening was performed with the C-4 aryl pyrimidinone nucleoside analogues, but none possessed any interesting activity. The study represents the first successful synthesis of C-4 aryl pyrimidinone nucleoside analogues by cross-coupling of arylboronic acids with an arylsulfonate derived from a pyrimidine nucleoside, as well as antiviral testing of this new class of compounds.
Keywords: CROSS-COUPLING REACTIONS; BORONIC ACIDS; 4-SUBSTITUTED 2(5H)-FURANONES; UNPROTECTED HALONUCLEOSIDES; PYRIMIDINE NUCLEOSIDES; ARYLBORONIC ACIDS; LEAVING GROUPS; PALLADIUM; DERIVATIVES; 2' -DEOXYNUCLEOSIDES